Saisir l’« Europe » à la lueur du discours officiel de l’UE : l’analyse de données au service d’une régionalisation critique de l’Europe - Etienne Toureille (Belgeo, 2020)
How to make the difference between a “European” state and a “non-European” state? This question is at the heart of the EU’s political project, which has already decided on this point to assess the candidacy of potential new members (case of Morocco in 1987). However, there is no way to objectively define what a European state is in official texts. And geography, like history or economics, does not propose a consensual definition to determine the content of this vague object that the EU would be called upon to embody: “Europe”. This article proposes to reverse the perspective: rather than seeking in ad hoc analyses a definition of this macro-region, it starts from the discourse produced by EU bodies to propose possible regionalizations of “Europe”. By using a combination of inductive and deductive methods from data analysis, this article will provide an opportunity to propose a critical and fuzzy regionalization of this political project. We will use this demonstration to take the chance to discuss the deep meaning of the act of regionalization.